Analysis of trend and sources of government budget deficit financing in Bangladesh - Sadekin, Md Nazmus; Alam, Md Mahbub; Al Abbasi, Al Amin; Saha, Subrata (Penerbit Universiti Utara Malaysia, 2020)
Budget deficit is one of the most significant macroeconomic issues which have been debated both in the academic and political arena since 1970s. This study aims to explore the current position of government budget deficit, its trends, and sources of budget deficit financing in Bangladesh, covering the duration between 1980 to 2018. Secondary data has been used which was collected from the Bangladesh Economic Review and the World Bank. Data has been analyzed through descriptive methods. The Government financing budget deficit from two sources like domestic and foreign sources. The study finds that Government finances most of its budget deficit from the domestic sources than foreign sources especially from non-banks sources due to the increase in the net sale of national savings certificates while borrowing from bank sources is on the decline. Along with the effective measures of generating more internal resources, the government should also focus on other areas to reduce the budget deficit. The government should be taking the approapriate steps to make progressively investable resources and generate a fund for financing the non-development spending in reducing the reliance on debt that can guarantee more distribution on the development sector